Penelitian pengembangan koleksi perpustakaan pada database Google Scholar: Narrative literature review - Mahesa, David Restu; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Jurnal Informatio, 2025)
Collection development in libraries is crucial to ensure that library resources meet user information needs. Librarians must adapt to advancements in information and communication technology in carrying out collection development activities. This study aims to identify research trends in library collection development in Asia through a narrative literature review, analyzing 12 relevant references from Google Scholar. The analysis focuses on library management and the evaluation of collection development policies. The findings reveal that collection development in Asian libraries varies based on user needs, culture, and the level of information technology. South Korea emphasizes collection digitization, Pakistan prioritizes academic needs, Indonesia faces budget constraints, India focuses on digital literacy, and East Asian countries integrate international networks. Collection development stages include user needs analysis, selection policy establishment, collection selection, material acquisition, weeding, and evaluation. Collection development policies emphasize providing relevant resources in digital and print formats, along with periodic evaluations to maintain quality. This study concludes that library collection development in Asia is a strategic effort to address the dynamics of information needs and enhance community literacy